Rancang Bangun Aplikasi Monitoring Barang Pada PT. Antar Nusa Teknik Sumbawa Berbasis Web - Nilam; Esabella, Shinta (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Antar Nusa Teknik Sumbawa operates in the electrical sector. The current inventory management at PT. Antar Nusa Teknik Sumbawa is still conducted semi-manually. This research aims to build a web-based inventory monitoring application that can display inventory management, stock levels, incoming goods, outgoing goods, and reports for PT. Antar Nusa Teknik Sumbawa. The research method was carried out in a staged and logical manner, using a qualitative approach for data collection through observation, interviews, and literature review. Software development utilized the Agile method. This application was built using the PHP programming language, MySQL database, and XAMPP tools. System testing was performed using the Black Box Testing method to verify the application's functionality. The research results indicate that the web-based inventory monitoring application has been successfully designed and built for input to PT. Antar Nusa Teknik Sumbawa, with the goal of providing convenience to PT. Antar Nusa Teknik Sumbawa in monitoring inventory in real-time, thereby increasing operational efficiency.